Sistema inteligente basado en agricultura 5.0 para automatizar el proceso de riego en la parroquia El Reventador, cantón Gonzalo Pizarro, provincia de Sucumbíos - Quishpi Condo, Johana Abigail (2025)
About 61% of the population in El Reventador canton, Gonzalo Pizarro, is dedicated to the cultivation of fruits, vegetables, grains, and other organic products. However, the irrigation systems used are based on manual and empirical practices, without considering the soil conditions and water needs of each crop. Therefore, this research designed and implemented a prototype of an intelligent system based on agriculture 5.0 to automatize the irrigation process. The research was carried out in 3 phases; the first phase consisted of a literature review and a diagnosis of the environment by means of interviews and technical visits. During the second phase, the appropriate physical devices and software were selected for the implementation of the prototype according to the defined requirements. Finally, the system’s performance was evaluated with field tests, experimenting in a 15m2 area of a 336 m2 bean field, comparing it with traditional method. We applied descriptive, field and experimental research. The results reveal a reduction in total water consumption of 32m3 of water, using the automatized system compared to the traditional one, with a slightly longer irrigation time of 13.53 minutes compared to 9.2 minutes respectively. In conclusion, the results show an improvement with the incorporation of technologies and information based on soil and crop parameters to optimize water use efficiency, as well as to adapt to other crops and rural environments with similar conditions.